On New High Order Quasilinearization Approaches to the Nonlinear Model of Catalytic Reaction in a Flat Particle - S. S. Motsa; O. D. Makinde; S. Shateyi (Advances in Mathematical Physics)
A novel computational approach known as pseudospectral quasilinearization (SQLM) is employed to tackle the two-point boundary value problem describing the reactivity behaviour of porous catalyst particles subject to both internal mass concentration gradients and temperature gradients, in endothermic or exothermic catalytic reactions. A comparison with the numerical results generated using the inbuilt MATLAB boundary value solver, bvp4c, for different values of the governing physical parameters is performed and an excellent agreement is achieved. A systematic way of improving the convergence of the SQLM is also presented.